Inventory And Potential Of Yellow Rice Stem Borer (Scirpophaga incertulas Walker) Parasitoid In Rice Plantation (Oryza sativa L) In Three Villages, Lima Puluh Regency, Batubara District, Northern Sumatra - Siagian, Sulastri; Siregar, Ameilia Zuliyanti; Tobing, Maryani C. (Akta Agrosia, 2020)
Yellow rice stem borer (YRSB), Scirpophaga incertulas Walker, often causes decreased of rice production. One of the pest controlling of YRSB used based on the concept of IPC (integrated Pest Control) was biological control using egg parasitoids. The purpose of this research was to find out the inventory and potential of parasitoids of eggs in yellow rice stem borer (S. incertulas) on rice cultivation at 3 locations (Kuala Gunung Village, Cahaya Pardomuan Village, and Air Hitam Village) in Lima Puluh Sub-District, Batubara Regency, Northern Sumatra. The study used a survey method by taking samples of groups of eggs by purposive sampling on rice cultivation. Egg clusters are kept for several days until the parasitoids appear. Parasitoid that appeared was preserved in a bottle containing 70% alcohol, then identification was carried out at the Pest Laboratory of Departmemt of Agrotechnology, Faculty of Agriculture, University of Sumatera Utara. This research was conducted from March to September 2019. The results obtained by 3 Parasitoid families were identified, such as Eulophidae, Scelionidae, and Trichogrammatidae. Parasitoid level and parasitoid dominance index were higher in the non-insecticide treatment compared to the insecticide treatment. The highest parasitic rate (41.78%) of the Eulophidae family and the lowest (0.00%) of the Trichogrammatidae family. The highest parasitoid dominance index (0.67) was found in the Eulophidae family and lowest (0) in the Trichogrammatidae family. The distribution pattern of the Eulophidae family was grouped, the Trichogrammatidae family was regular while the Scelionidae family was different for each village. Our prediction, the research will be useful for future.Keywords: Rice, Scirpophaga incertulas, parasitoid, parasitation Level, dominance, distribution pattern.